Adaptive propensity score procedure improves matching in prospective observational trials - Kronsteiner, Dorothea; Uhlmann, Lorenz; Schönenberger, Silvia; Kieser, Meinhard (BMC medical research methodology, 2019)
Randomized controlled trials are the gold-standard for clinical trials. However, randomization is not always feasible. In this article we propose a prospective and adaptive matched case-control trial design assuming that a control group already exists.